Adsorption performance of basic fuchsin on alkali-activated diatomite. Issue 5 (July 2020) - Zhao, Yong-Hua; Geng, Jin-Tao; Cai, Jie-Chuan; Cai, Yu-Fu; Cao, Chun-Yan
The natural diatomite was treated with NaOH to obtain alkali-activated diatomite. The materials were systematically characterized by X-ray powder diffraction, X-ray fluorescence, Fourier transform infrared spectroscopic, scanning electron microscopy, and N2 adsorption–desorption. Meanwhile, the potential use of alkali-activated diatomite as adsorbent for the removal of basic fuchsin from aqueous solution was assessed by batch experiment. Results indicated that the structure and textural properties of diatomite were obviously changed via alkali activation, and then affecting its adsorption performance. The adsorption capacity of alkali-activated diatomite for basic fuchsin was higher than that of natural diatomite. In the case of alkali-activated diatomite, its adsorption capacity was increased with increasing the activation temperature, and the diatomite activated at 115°C (alkali-activated diatomite-115) exhibited the maximum adsorption capacity. The pseudo-first-order kinetics and the Sips isotherm model were preferable to describe the adsorption process of basic fuchsin on alkali-activated diatomite-115 and the thermodynamic parameters indicated that the adsorption process was endothermic and spontaneous.